Effect of ignition energy on combustion characteristics of flammable working fluids. (1st March 2023) - Chen, Yubo; Yang, Zhao; Lv, Zijian; Zhang, Yong; He, Hongxia
Graphical abstract: Highlights: The change laws of flammability limits with ignition energy for flammable working fluids are studied. The influence laws of ignition energy on flame propagation are acquired. The burning velocity in stable propagation stage is independent of ignition energy. The influence mechanism of ignition energy on combustion characteristics is obtained. Abstract: Working fluids with low global warming potential (GWP) will play an important role in the research and development of alternative working fluids for organic Rankine cycles and refrigeration cycles. However, the flammability of low GWP working fluid limits their development, and the energy of typical fire sources has a significant impact on their safe application. At present, there is a lack of relevant research on the effect of ignition energy on their flammability. In this paper, the effect of ignition energy on the combustion characteristics for propane (R290), fluoroethane (R161), 1, 1-Difluoroethane (R152a), and 3, 3, 3-Trifluoropropene (R1243zf) was studied using a variable ignition energy system. The initial flame propagation process, flammability limit, and burning velocity were tested and analyzed in the range of 50 mJ to 20 J. The results showed that with the increase of ignition energy, the lower flammability limit (LFL) decreased and the upper flammability limit (UFL) increased, but their rate of change decreased with the increasing ignition energy. The effect of ignition energy on the flammability limit of R1243zf was significantly greater than that of the other three working fluids. In addition, the effect of ignition energy on flame propagation was mainly limited to the initial stage, and the burning velocity was independent of ignition energy. The mechanism of ignition energy on combustion characteristics was obtained. The research results have guiding significance for the safe application of flammable working fluids.